Isolation of Bacterial Endophytes Associated with Cinchona ledgeriana Moens. and Their Potential in Plant-growth Promotion, Antifungal and Quinoline Alkaloids Production - Masita, Rahmi; Aryantha, I Nyoman Pugeg; Noh, Nur Izzati Mohd; Anugrah, Fauzi Akhbar; Zubaidah, Siti (Journal of general and applied microbiology, 2024)
For centuries, quinoline alkaloids from the tree bark of Cinchona ledgeriana (C. ledgeriana) have been used in the treatment of malaria. However, unsustainable harvesting and poor growth conditions greatly limit its use as raw materials. Since plant endophytes are known to contribute to the physiology of the host and its metabolism for survival, this study showed the potential of endophytes isolated from C. ledgeriana roots in promoting the germination of Catharathus roseus (C. roseus) seedlings and the biosynthesis of quinoline alkaloid. In this present study, we found that the Enterobacteriaceae family comprised the majority of the bacterial community, with Klebsiella pneumoniae being the most abundant species at the C. ledgeriana roots. Characterization of culturable bacterial endophytes from the C. ledgeriana roots showed that all the isolates displayed plant growth-promoting factors and antifungal activities. Interestingly, chromatographic analyses led to the identification of the quinoline alkaloids producing Achromobacter xylosoxidans (A. xylosoxidans) A1. Moreover, the co-cultures of A. xylosoxidans A1, Cytobacillus solani (C. solani) A3, and Klebsiella aerogenes A6 increased the fresh and dry weight of the C. roseus seedlings. These results suggest that these bacterial endophytes may enhance quinine and quinidine production as well as the growth of the plant host.